Normalizing extreme work in the Police Service? Austerity and the inspecting ranks. (July 2015) - Turnbull, Peter J.; Wass, Victoria
Using rich and extensive data collected from police Inspectors over an extended period (2011–2014), this study explores two research questions that seek to (1) define extreme work in policing and (2) understand how it is maintained and reproduced. For some, by definition, the work of the emergency services is understood to be extreme, but the urgent and dangerous elements of policing form only a small part of an Inspector's job and for these incidents they are well-trained in advance and well-cared for afterwards. When police Inspectors describe their work in times of austerity, it is not the emergency aspects that they experience as extreme work. Rather, it is the intensity of work over long hours above contract, which are both involuntary and unrewarded. In seeking to understand what drives extreme work and why it is accepted, especially when it is not preferred, not paid for and has detrimental effects on health and wellbeing, we uncover a process of institutional maintenance through which over-work: (1) is intensified via the extra demands imposed by austerity; (2) is maintained through work practices, a strong professional identity and a masculine police culture; but (3) is not 'normalized' in the sense of being embraced or celebrated by police Inspectors.